Pengaruh Kombinasi Pupuk Kandang Sapi dan Pupuk NPK terhadap Pertumbuhan dan Hasil Tanaman Kubis (Brassica oleraceae L.): The Combination Effects of Cow Manure and NPK Fertilizer on Cabbage’ (Brassica oleraceae L.) Growth and Yield - Ramli Ramli; Fitri Hidayati Arzad (University of Darussalam Gontor, Ponorogo, East Java Indonesia, 2024)
The use of organic and inorganic fertilizers is an alternative way to get good cabbage production, one of which is by using cow manure and NPK. This study aims to determine the good use of a combination of cow manure and NPK fertilizer on the growth and yield of cabbage (Brassica oleraceae L.). The research was carried out from October 2022 to January 2023. This study used a Randomized Block Design (RAK), namely with a combination of cow manure (PKS) and NPK fertilizer. With the following details: P0 = Control, P1 = PKS 200 g + NPK 5 g, P2 = PKS 400 g + NPK 10 g, P3 = PKS 600 g + NPK 15 g, P4 = PKS 800 g + NPK 20 g. The treatments were repeated 3 times so that there were 15 experimental units. Each experimental unit used 5 polybags and each polybag was planted with one plant so that the total cabbage plants used were 75 plants. The variables observed were leaf area, time of crop formation, crop weight, and crop volume and root volume. The results showed that the combination of cow manure and NPK fertilizer had a significant effect on the growth of leaf area, crop weight, and crop volume. However, it has not had a significant effect on the time of crop formation. Treatment of cow manure 800 g + NPK 20 g (P4) fertilizer increased crop weight and crop volume. Treatment of cow manure 400 g + NPK 10 g (P2) fertilizer increased cabbage leaf area.